Problems of Harmonization of the Normative Basis in the Sphere of the Sanitary Protection of the Territory of the Russian Federation with the Requirements of the World Trade Organization Agreements - A. E. Shiyanova; V. P. Toporkov; S. N. Lutsenko; T. K. Merkulova; L. D. Shilova (Проблемы особо опасных инфекций, 2008)
Harmonization of the national normative methodical basis of the Russian Federation in the sphere of the sanitary protection of the territory with the IHR (2005) will simultaneously signify its harmonization with the requirements of the World Trade Organization Agreements and will not lead to the contradiction with them. Requirements contained in the normative documents referring to the sphere of the sanitary protection are priority ones regarding to the regulations of the World Trade Organization documents as they touch upon public health protection. The standard duration of the procedure of the sanitary and quarantine control of cargo transport, goods and cargos should be foreseen in the methodical documents.